A spatiotemporal Order-Revealing query processing approach for Industrial Internet of Things - Ravi Sharma; Balázs Villányi (Journal of King Saud University: Computer and Information Sciences)
Industrial Internet of Things (IIoT) is one of the most audacious emerging technologies, with numerous applications across multiple industries. As a basic technology of the IIoT, two-tier mobile sensor networks (TMWSNs) are designed with storage-abundant storage nodes intended to be placed as an intermediate tier for collecting sensory data and responding to the queries. Nonetheless, there is a significant risk that the storage nodes will be compromised, resulting in not only a privacy issue, but also incorrect or incomplete query results. In this paper, we investigate the authenticity and integrity of query results in a TMWSNs-based IIoT system and propose a spatiotemporal Order-Revealing query processing approach. Extensive simulation results show that our proposed scheme is both effective and energy efficient as compared to existing state-of-the-art schemes.